The Impact of the Fit for 55-Regulation on Airfares - Thorsten Ehlers; Katrin Kölker; Klaus Lütjens (Wirtschaftsdienst)
Abstract The European Union seeks to reduce carbon emissions 55 % compared to 1990 rates by 2030. The instruments that are intended to support this reduction are a tightened Emission Trading Scheme (EU-ETS), a mandatory blending of jet fuel with sustainable aviation fuel (SAF), and a minimum tax on energy carriers (Energy Taxation Directive, ETD). In this article, we analyse the impact of these instruments on airfares in different markets: within Germany, between Germany and other European countries, as well as international connections to Asia, Africa and North America. Furthermore, we compare the impact between different carrier types: network carriers, touristic carriers and low-cost carriers.